Bacteriological studies for Kranji catchment - Por, Yu Ling. (2009)
With the introduction of ABC Waters Programme by Singapore’s Public Utilities Board (PUB), Kranji Reservoir and some of its surrounding water bodies will be used for recreational purposes. The purpose of this project is to determine whether the water bodies surrounding Kranji Reservoir are safe for recreational activities. Possible point and non-point sources contributing high levels of bacteria within the Kranji Catchment are identified. Reasons as to why some of these locations are contributing high bacteria concentration are discussed. Any correlations between bacteria levels during dry and wet weather are also examined.